Valuasi Ekonomi Hutan Mangrove di Pulau Untung Jawa Kepulauan Seribu : Studi Konservasi Berbasis Green Economy - Dandy E Prasetiyo; Firman Zulfikar; Shinta Shinta (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2016)
Promoting forest as one of green economy asset in Indonesia become an important agenda in the process of development. Forests have an important role as a source of foreign exchange and also as a form of natural resource wealth. The era of globalization with the accelerated economic growth increases the need for both, the fields of agriculture, infrastructure, land requirements and other sectors. Increased human needs are giving a positive correlation to the increased pressure on forests. Mangrove forests as one of the most productive ecosystems in the world are also experiencing the same threat. The expansion of settlements and ponds in coastal areas lead to degradation of mangrove forests is very high. The economic value of mangrove forests of diverse functions such as shoreline protection, habitat for aquatic organisms, carbon storage, and a variety of other functions has not been a lot of concern to the public and policy makers. This study aimed to quantify the economic value of mangrove forests in Untung Jawa Island, Thousand Islands as an effort to support the government's program to realize the green economy in the forestry sector. Method of economic calculation mangrove forests in this research is to calculate the Total Economic Value / Total Economic Valuation (TEV), which consists of direct use values (Direct Use Value) and indirect use values (Indirect Use Value). The results showed that the direct use value of mangrove forests in Untung Jawa Island is Rp. 395,126,912 which includes the value of timber, fruit value, and the value of the fishery, while the indirect use value is Rp. 7,500,600,000 calculated from the value of coastal protection, the value of foraging, conservation value, educational value, and recreational value. The total economic value (total economic value) of mangrove forests in Untung Jawa Island reached Rp. 7,895,726,912Keywords : mangrove, green economy, total economic valuation